Assessment of the competencies of the Filipino food and beverage crew in the cruise industry - Camalig, Jocelyn Young
The study aimed to assess the Food and Beverage Service competencies required by the cruise industry and determine if they match with the curriculum being offered by the subject institutions. Respondents included F and B Managers/ Supervisors and Crew members of selected manning agencies; and the administrators, faculty and students of three universities offering the BSHRM-CLO program. Results show that the subject manning companies preferred F and B crew members who are male, single, aged between twenty to twenty one years old for new employees, preferably college graduates, physically fit and at least five (5) feet and six (6) inches. On the skills required by the cruise industry, the two groups of respondents agreed that service encounter with guests rank first among the tasks of F and B crew. They also claimed that complying with company policies and environmental policies at sea is important. Knowledge on proper grooming and sanitation topped the lists for F and B crew while pre-service, actual service and post-service procedures are more important for the Managers/ Supervisors. For attitude, both respondents found "being present at work always" as necessary. The F and B crew regarded punctuality as also important while the F and B Managers/ Supervisors, attitudes that give utmost satisfaction to guests. Among Filipino values that would enhance performance, respect and enthusiasm topped list for F and B crew and Managers/ Supervisors respectively. Mann-Whitney U at significance level of 0.05 shows significant difference among the twenty six tasks performed in Food and Beverage. Out of these tasks, the supervisors/managers regarded the need for training and development for twelve tasks. The latter include presenting the menu properly, making table reservations properly and applying appropriate first aid treatment to injured guests. Subject institutions saw the need to improve the curriculum, facilities, industry linkage and to upgrade the faculty competencies. Most of the competencies were developed or enhanced only by Pri-1 and Pri-2 while Pri-3 needs to improve on its curriculum. There should therefore be a strong linkage between the academe and the cruise industry through an intensive training and development programs and regular immersion for Managers/ Supervisors and the F and B crew. More intensive and focused studies on the competencies for BSHRM-CLO graduates should be conducted by a technical panel composed of representatives from the industry and the Commission on Higher Education (CHED). The curriculum should include a multi-cultural management subject to address the problem on cultural diversity.